The influence of the shaft angle value on the normal stress and displacement repartition by bevel gear pairs − a TCA investigation - Bodzás, Sándor (Mechanics & industry : an international journal on mechanical sciences and engineering applications, 2020)
Five types of bevel gear pairs having straight teeth were designed to analyze the effect of the modification of the shaft angle. This angle is the parameter − subject of TCA. After the geometric design process and the creation and assembly of the CAD models, Tooth Contact Analysis (TCA) was performed in order to get the mechanical parameters focusing of the tooth roots of the connecting teeth. We repeated this process five times since the load torques were also changed. The received mechanical parameters on the teeth connection of the pinion and the driven gear were analyzed with taking in consideration all four-tooth root surfaces that limit the contacting teeth pair. Finally, we referred to the useful selection of the appropriate gear pair for the engineering application.